Courageous women in Greek and Nigerian drama: antigone and tégónni (2016)
This paper compares Sophocles’ treatment of courage in Antigone and in Femi Osofisan’s Tègqnni demonstrating the power of women in contrast to the perception of women. In both the Classical era and Yoruba traditional society, it was rare for a woman to speak in public or disobey a man. They were expected to remain silent while men spoke and managed the affairs of the state. The courageous actions of women were considered acts of disobedience to the gender expectation of women in the society since women were not expected to live a public life like men; they were to obey their male relatives. Antigone and Tegònni, as portrayed by Sophocles and Osofisan respectively, acted against the laid down traditions that depict women as being physical and intellectually weak. The women stood up for themselves, facing the difficult situation like fearless warriors. This paper is a comparative analysis that examines the issue of portrayal of courage in women against the value systems of both cultures particularly in contemporary drama. !t elucidates the role of the dramatist in exposing the ills of the society through the portrayal of the agonies of women using the texts of Sophocles and Osofisan’s Antigone and Tègònni respectively